ANALGESIC ACTIVITY OF TELMISARTAN AND ROSUVASTATIN IN VARIOUS ANIMAL MODELS - S, Anand; M, Sangavai; R, Parthiban; J, Anu Rita (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Aim: To study the analgesic activity of telmisartan and rosuvastatin in various animal models Materials and Methods: Analgesic activity of telmisartan and rosuvastatin alone and in combination is assessed in hot plate method in rats; acetic acid induced writhing in mice and tail clip method in rats, in all these tests the comparator is aspirin. Results: In hot plate method rosuvastatin showed some analgesic activity, while telmisartan is almost nil. Effect of the combination group in causing analgesia is almost similar to that of aspirin producing more than 70% inhibition of writhing. In tail clip method to test the mechanical pain stimulus both aspirin and combination group had 50% inhibition of response to application of tail clip. Conclusion:Â  These results shows that rosuvastatin has some analgesic activity and it is stronger when combined with telmisartan, but this may not justify its use as standalone analgesics. Though it can be a potential adjuvants for coexisting inflammatory disorders and dyslipidemia, hypertension.